DEGRADATION OF WEEDS CROPS BY CELLULOLYTIC BACTERIA ISOLATED FROM EARTHWORM - I W., Suberata; Mudita, I M.; Sutama, I N. S. (Jurnal Peternakan Tropika, 2017)
Evaluation of ability on degrading agricultural waste by eight cellulolytic bacteria isolated from earthworm ( Lumbricus rubellus ) had been carried out for have the best cellulolytic bacteria as weeds crops degrader. The experiment was conducted with completely randomized design (CRD) 8 treatments and 3 replications, treatments based on the eight cellulolytic bacteria isolates with the code EB 1 CL, EB 2 CL, EB 3 CL, EB 4 CL, EB 5 CL, EB 6 CL, EB 7 CL and EB 8 CL.Evaluated of degrade ability measure by diameters of clear zone on agricultural waste were rice straw, rice bran, water hyacinth and water lettuce leaves. The results showed that cellulolytic bacteria isolated from earthworm coded EB 1 CL has produce highest clear zone diameters (P <0.05) on rice bran and water lettuce leaves substrate of 1,351 cm (Vs 1,239 - 1,331 cm) and 1,727 cm (Vs 1,621 - 1,721 cm), whereas the bacteria isolate coded EB8CL has produce highest clear zone diameter (P <0.05) on rice straw and water hyacinth substrates that were 1.060 cm (vs. 1.010 - 1.053 cm) and 1.495 cm (vs 1.394 - 1.494 cm). The bacteria isolates coded EB2CL had the lowest degradation ability on all substrates measured. Based on the result of this research, it can be concluded that cellulolytic bacteria isolate from earthworm with code EB1CL and EB8CL have the best ability in degrading of agricultural waste. Key words: Cellulolytic Bacteria, Earthworm, Ability on degrading substrates, Agricultural Waste